2009
DOI: 10.1080/03630240802708523
|View full text |Cite
|
Sign up to set email alerts
|

Women's Perceptions of Influences on Their Mood

Abstract: These subjective data suggest that women perceived a wide range of external, usually interpersonal, influences as relevant to their mood, however menstrual cycle was rarely mentioned. Perceptions of influences on mood are statistically related to frequency of moods. In addition, ethnicity and paid employment are independently associated with positive mood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…These finding are consistent with the first phase of the MiDL study, in which 507 non-help-seeking women were surveyed about what factors they perceived to influence their daily moods. Results showed that 46-61.9% of women perceived stress, and 52.1-65.9% of women perceived physical health to influence their daily positive and negative moods "a lot" (Romans et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These finding are consistent with the first phase of the MiDL study, in which 507 non-help-seeking women were surveyed about what factors they perceived to influence their daily moods. Results showed that 46-61.9% of women perceived stress, and 52.1-65.9% of women perceived physical health to influence their daily positive and negative moods "a lot" (Romans et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…To better understand the role of psychosocial factors in women's mood we included three other measures in our models: Social Support, Stress and Physical Health. These have been shown to have substantial influence on mental health (Helliwell and Putnam, 2004;McEwen, 2001;Romans et al, 2009) and were used as comparison variables against which to assess the strength of the association between ovarian hormones and daily mood. We included additional models to explore whether hormone levels from 1 to 5 days prior might also influence daily mood.…”
Section: Introductionmentioning
confidence: 99%
“…Participants were recruited into the Mood in Daily Life (MiDL) study, a larger study to examine self-reported mood changes across the menstrual cycle [24]. Potential participants were contacted via telephone by a professional random-digit dialing service, and they were completely informed about the study protocol and objectives; the focus of the study on the menstrual cycle was obscured to avoid potential priming effects [25].…”
Section: Participantsmentioning
confidence: 99%
“…There is an urgent need for adjunctive/alternative treatments for chronic depressive symptoms in pregnancy, particularly those which target prevention of relapse/ recurrence [36,37,42].Considerable literature supports PA as a therapeutic modality for depressive and related symptoms [43,44].Results from a Cochrane review and other meta-analyses suggest that PA has effects on depressive symptom management comparable to antidepressant medications and cognitive behavioral therapy [45,46]. However, individuals with depressive symptoms have reduced self-regulation and self-efficacy related to PA and report great difficulty following-through with PA behaviors [47,48].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, many women remain under-or un-treated due to the actual and perceived risks involved in pharmacological therapy during pregnancy [5]. Even with UC, a majority of individuals do not achieve partial or full symptom remission [33][34][35][36][37]. For example, one meta-analysis suggests only a 12-16% response rate to antidepressants in individuals with moderate to severe depressive symptoms with a slight improvement with the addition of other therapeutic modalities, such as cognitive-behavioral therapy [38].…”
Section: Introductionmentioning
confidence: 99%